An expanded cortical representation for hand movement after peripheral motor denervation. - Reddy, H; Bendahan, D; Lee, M; Johansen-Berg, H; Donaghy, M; Hilton-Jones, D; Matthews, P (2002)
OBJECTIVES: Functional reorganisation of the motor or sensory cortex has been demonstrated in animals after section of mixed peripheral nerves. Here functional changes in the motor cortex specifically after peripheral motor denervation in humans are investigated. METHODS: Functional MRI (fMRI) was used to study brain activation during a finger flexion-extension task in patients with a late onset, acquired pure motor neuropathy (n=6), contrasting results with those from patients with pure sensory neuropathies (n=4) or healthy controls (n=7). RESULTS: Increases in the extent of activation in the motor cortex both ipsilateral and contralateral to the hand moved were found in the patients with motor neuropathy. The neuroanatomical localisation of the mixed contralateral sensorimotor cortex activation volume was more posterior for the patients with motor neuropathy than for the healthy controls (mean difference, 12 mm, p<0.05). The pure sensory neuropathy group by contrast showed no change in the extent of activation relative to healthy controls and a trend for more anterior primary sensorimotor cortex activation (p<0.06). To test whether the increased activation volumes found in patients with motor neuropathy were a result simply of factors such as increased effort with movement rather than the motor denervation, patients with hand weakness from inclusion body myositis (n=4) were studied while making similar hand movements. No differences in either the numbers of significantly activated voxels or in their localisation were found relative to healthy controls (n=10). CONCLUSIONS: These results provide a novel demonstration that peripheral denervation (as distinguished from factors related to weakness) leads to functional reorganisation of the sensorimotor cortex in the adult brain. This suggests that adaptive responses to motor denervation involve the central as well as the peripheral nervous system.